2007
DOI: 10.1158/1078-0432.ccr-06-0964
|View full text |Cite
|
Sign up to set email alerts
|

Phase I Clinical Trial of STA-4783 in Combination with Paclitaxel in Patients with Refractory Solid Tumors

Abstract: Purpose: STA-4783 is a new compound that markedly enhances the therapeutic index of paclitaxel against human tumor xenograft models. A phase I clinical trial was undertaken to determine the maximum tolerated dose, toxicity profile, and pharmacokinetics of STA-4783 in combination with paclitaxel. Experimental Design: Adults with refractory solid tumors concurrently received STA-4783 and paclitaxel as a 3-h i.v. infusion at starting doses of 44 and 135 mg/m 2 , respectively. After increasing paclitaxel to 175 mg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
78
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(83 citation statements)
references
References 15 publications
(8 reference statements)
1
78
0
1
Order By: Relevance
“…In a phase I clinical trial of elesclomol in combination with paclitaxel for patients with refractory solid tumors, elesclomol was well tolerated and did not increase toxicity [31]. We showed that elesclomol had no cytotoxicity in normal breast epithelial cells, consistent with the results from clinical trials [1,2].…”
Section: Discussionsupporting
confidence: 84%
“…In a phase I clinical trial of elesclomol in combination with paclitaxel for patients with refractory solid tumors, elesclomol was well tolerated and did not increase toxicity [31]. We showed that elesclomol had no cytotoxicity in normal breast epithelial cells, consistent with the results from clinical trials [1,2].…”
Section: Discussionsupporting
confidence: 84%
“…Many developmental redox therapeutics have shown a potentiating effect on pharmacodynamic activity of other anticancer agents and radiation, but offer only modest or no chemotherapeutic benefit if used as single agents (9,29,193). Therefore, many ongoing clinical studies test activity of these agents as combinatorial drugs, consistent with the mechanism of action that involves induction of deviations from redox homeostasis that preferentially sensitize cancer cells to the cytotoxic effects of chemotherapeutic agents (9,29,232,246,288). However, other ongoing studies examine feasibility of single agent redox chemotherapy as detailed throughout this review.…”
Section: Redox Chemotherapeuticsmentioning
confidence: 99%
“…4-38), a symmetric thiobenzoylhydrazide-derivative [Nmalonyl-bis (N 0 -methyl-N 0 -thiobenzoylhydrazide, STA-4783), was originally derived from a differential phenotypic screen that assessed potentiation of in vitro cytotoxicity of paclitaxel against human tumor cell lines (29,118,193). Early preclinical studies indicated that the growth of human tumor xenografts in CD-1 nude mice was unaffected by treatment with elesclomol administered as single therapeutic agent (7,25,26).…”
Section: H In Search Of a Molecular Target: Elesclomolmentioning
confidence: 99%
“…Another compound under investigation for use in metastatic melanoma is STA-4783, which has been found to dramatically enhance the antitumor activity of paclitaxel without increasing host toxicity [38]. STA-4783 is a bisthiobenzoylhydrazide compound and an inducer of heat shock proteins.…”
Section: Unique Kinetics Of Response With Ipilimumab Therapymentioning
confidence: 99%